Direito educacional: o poder judiciário e a efetivação de políticas públicas no Brasil - Bradbury, Leonardo Cacau Santos La (2013)
The present study aims to investigate the proceeding of the Judiciary in the effectiveness and improvement of the educational public policies elaborated by the Executive and Legislative by law and interim measures. We will begin analyzing the right of education in their general aspects, provided in all Brazilian constitutions. Following will establish the concept and purpose of public policies, explaining to the reader the meaning of the expression Politics Judicialization . After we will talk about the constitutional principles of Brazilian education and, ultimately, will be analyzed some educational public policies in which there was the role of the Judiciary to improved and adapted them to the constitutional principles and guidelines set out in the Federal Constitution of 1988.